Pengaruh Kualitas Pelayanan Model Carter Terhadap Kepuasan Nasabah Bank BTPN Syariah Area Kota Jambi - Musdalifah .; Rafiqi .; Arfah . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to determine the effect of CARTER dimensions in service quality on the level of customer satisfaction of Bank BTPN Syariah in the Jambi City area. This study uses a quantitative research method with data collection through questionnaires. The sample studied was 100 customers. In analyzing the data, the author used multiple linear regression analysis using the SPSS version 27 program.The results of the analysis obtained from this study indicate that Compliance has a positive and significant effect on customer satisfaction. Seen from the t test with a significance of <0.001 from <0.05, with a calculated t value of 4.430. Assurance has a positive and significant effect on customer satisfaction. Seen from the t test with a significance of 0.006 <0.05, with a calculated t value of 2.800. Reliability has a positive and significant effect on customer satisfaction. Seen from the t test with a significance of 0.043 <0.05, with a calculated t value of 2.051. Tangible Evidence has a positive and significant effect on customer satisfaction. Seen from the t-test with a significance of <0.001 from <0.05, with a calculated t value of 3.756. Empathy has a positive and significant effect on customer satisfaction. Seen from the t-test with a significance of <0.001 from <0.05, with a calculated t value of 3.432. Responsiveness has a positive and significant effect on customer satisfaction. Seen from the t-test with a significance of <0.001 from <0.05, with a calculated t value of 3.959. The responsiveness variable has a greater dominant influence on customer satisfaction and the variable that is not dominant is the reliability variable.